Effects of impregnation to the porosity of activated carbon / Fazlin Meor Hussin - Meor Hussin, Fazlin (2000)
The purpose of this project is to find out the effect of impregnation to the porosity of activated carbon using two techniques, i.e., spray and immersed method. The samples from coconut shell based of GAC were characterised using ASAP 2000 for area and volume, Methylene Blue method and lodine Number before and after impregnation. Parameter for both of the method was the contact time. The result shows that the surface areas of activated carbon were changed due to the impregnation process. The spray method has a significant effect to the porosity of activated carbon.